Maskulinizm, radykalna polityka i pożytek z wyobraźni: pragmatyzm a feminizm w ujęciu Richarda Rorty’ego - Jurszo, Robert (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2007)
The author devotes the present paper to Rorty’s statement that pragmatism offers a significantly better support for the feminist movement than any version of metaphysical philosophy. Thus the author is preoccupied with the issue of what tangible advantages feminists might obtain (according to Rorty), if they refer to the rhetoric created by American pragmatism in their disputes with their intellectual opponents and their attempts to alter social reality. However, not all feminists will find the pragmatism promoted by Rorty useful. For example, feminists operating within the framework of the Catholic Church would certainly not be able to use it. The gap between this type of spirituality and the proposals of American philosophers is too wide. What seems particularly valuable in Rorty’s version of feminism (and what constitutes an integral part of its neopragmatism) is a strong emphasis on the role of imagination opposed to analytical reason, and the superiority of the former.